Pengembangan Bahan Ajar Teks Cerita Pendek Dengan Memanfaatkan Aplikasi Ispring Dalam Mata Pelajaran Bahasa Indonesia Untuk Kelas IX SMP PGRI Poncokusumo - Afwa Zumrotur Ro`Ifah; Artifa Sorraya; Susandi (Universitas Insan Budi Utomo, 2024)
Teaching materials are one of the important aspects in the world of education, because teaching materials are one of the means to support the running of the learning process. Based on observations in class IX of PGRI Poncokusumo Junior High School in Indonesian lessons, especially in short serita material, there are several problems encountered by researchers, namely, difficulty in understanding lessons, still lack of motivation and student boredom during the learning process. This study aims to determine how the feasibility of short story text teaching materials by utilizing the iSpring Suite application, language feasibility in short story text teaching materials by utilizing the iSpring Suite application and the feasibility of short story text teaching steel designs by utilizing the iSpring Suite application in class Indonesian subjects of PGRI Poncokusumo Junior High School. The research used is research and development (R&D) method. This research method is a research method that aims to design, develop learning programs and products that can meet the criteria. The product produced in the research is in the form of short story text learning videos by utilizing the ispring suite application that is suitable for use. The feasibility of teaching materials is seen from the values given by linguist validators, material expert validators and design expert validators produced by diantaraya, getting scores for linguist validation results of 3.85, for material expert validation 2.81 and validation results from design experts 3.72 so that a total average overall validation score of 3.46 with very valid categories is obtained